DETERMINAN KINERJA PEGAWAI: PERAN BEBAN KERJA, MOTIVASI DAN KEPUASAN KERJA - Kurniawan, Aris Hidayat; Prasilowati, Sri Lestari; Suyanto, Suyanto (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2019)
This study aims to examine the relationship perceived high workload, job motivation and job satisfaction on performance. Research conducted at the Office of Cileungsi First’th Tax Service by taking 89 employees as the research sample. Quantitative research was conducted by describing and verification data. Multiple linear regression analysis is the statistic approach to data analysis. The study produced three major findings consistent with the hypothesis put forward, that is: (1) the workload of employees are in the high category, (2) work motivation is in the high category, 3) job satisfaction is in the high category and the performance is in the medium category. Base on research finding, in order to increase employee performance, can be done by managing the workload of employees, increase work motivation and increase job satisfaction. Keywords : Workload, Job Motivation, Job Satisfaction and Performance